2023
DOI: 10.4236/jhepgc.2023.92032
|View full text |Cite
|
Sign up to set email alerts
|

The Quantum Chromodynamics Gas Density Drop and the General Theory of Relativity Ether

Abstract: β decay is one of the most fundamental and thoroughly studied nuclear decay. Surprisingly, the β decay rates were found to have a periodic time variability [1]. However, others argued that there is no evidence for such cyclic deviation from the exponential first order kinetics decay law [2]. Here we propose that the β decay is a pseudo-first order exchange reaction triggered by uddu   exotic mesons and propose a QCD gas theory. In analogy to the atmospheric gas density, the proposed QCD gas density drops wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…We propose that the QCD vacuum pion tetrahedron condensate [9] density in space is non-uniform and should drop in the KBC giant voids in analogy to earth's atmospheric density drop [10]. We propose to calculate the gravitation acceleration from the non-uniform pion tetrahedron condensate density variation.…”
Section: Non-uniform Qcd Vacuum Quark Condensatementioning
confidence: 99%
See 2 more Smart Citations
“…We propose that the QCD vacuum pion tetrahedron condensate [9] density in space is non-uniform and should drop in the KBC giant voids in analogy to earth's atmospheric density drop [10]. We propose to calculate the gravitation acceleration from the non-uniform pion tetrahedron condensate density variation.…”
Section: Non-uniform Qcd Vacuum Quark Condensatementioning
confidence: 99%
“…In a previous paper [9] we assumed that the QCD vacuum pion tetrahedron condensate drops like the atmospheric density due to gravity as shown in the Figure 1 on the left-hand side. We proposed that similar to the gas kinetic theory, the pressure difference on a virtual box top and bottom surfaces that contains an infitisimal volume of the pion tetrahedron condensate is due to the difference in the number of collisions at the top and the bottom surfaces due to the non-uniform pion tetrahedron condensate density induced for example by a massive stars, where M is the star mass, r is the distance from the star, and ρ is the pion tetrahedron condensate density.…”
Section: Extremely Low Pion Tetrahedron Condensate Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous papers [9] [10] [11], we suggested that antimatter plays a principal role in the universe and that antimatter is inseparable from both matter and space. We suggested that a QCD gas comprised of even number of quarks and antiquarks, the uddu   tetraquark, fill space and perform quarks and antiquarks pair exchange reactions with matter particles.…”
Section: Big Bang and Quasi-steady-state Cosmologymentioning
confidence: 99%
“…Here, we propose that the B2W hole quantum tunneling transition may be accelerated crossing the reaction energy barrier by the antimatter trapped in the Journal of High Energy Physics, Gravitation and Cosmology BH ergoregions [9] that act as a detonator releasing a huge amount of mass and heat in the explosion and a BH spray.…”
Section: Black Hole Spray and The Cosmic Webmentioning
confidence: 99%